Fear of terrorism: Legislation and perceived loss of civil liberties - Richardson, Finola (2010)
Terrorism is a fear-inducing element of the current Australian political agenda. There are concerns about counter-terrorism legislation employed in Australian since the September 11th attacks on the United States, (9/11) and the effects these laws have on the civil liberties of Australian citizens. The literature presents two views one identifies the low risk of terrorism in Australia as no justification for strict new legislation. An alternative claim is increased security following 9/11 is essential in ensuring Australia is not viewed as a 'soft target'. The psychological experience of fear following terrorist attacks can influence the public's response to Government initiatives regarding security. The aim of the current study was to explore the experiences of terrorism-related-fear, perceptions about security and the counter-terrorism legislative effects on the civil liberties of Western Australians. Using a phenomenological approach, semi-structured interviews were conducted with eight men and six women of various ages. Interpretative phenomenological analysis (IP A) was used in the analysis phase. Five major themes emerged relating to participant's levels of fear, ideas about security and civil liberties; psychological effect of 9/11, risk, security, social identity and civil liberties and perceived effect. The findings suggest terrorism-related-fear was moderate in participants, and they did not feel concerned about legislation impacting their civil liberties, as they recognised some civil liberties needed to be sacrificed in order to achieve desired safety levels